Role of water taken from different environments on the ability of Pseudomonas aeruginosa to form biofilm on abiotic surfaces - Raghad S. Mouhamed; Mohammed Mosa Jafaar; Mohammad H. Hafudh; Lamees M. R. Abbas; Mohammed Mohsin Aziz; Mahmood Jalil Ahmad; Huda Mohsan; Heiba Simer; Ghafil, Jenan Atiyah Ghafil; Shaymaa Hussein Hassan; Ayaid Khadem Zgair (World Journal of Experimental Biosciences, 2014)
Pseudomonas aeruginosa readily binds to different kind of abiotic surfaces and form biofilm. The ability of the bacterial species to form biofilm onto polyvinyl chloride (PVC) is associated with several economic, health and environmental problems. The effect of kind of water on ability of this bacterium to form biofilm is scanty in literature. In present study, the ability of different environmental isolates of P. aeruginosa to form biofilm onto polystyrene microtiter plate was evaluated. Furthermore, the effect of waters that collected from different sources on biofilm formation of this bacterium onto PVC was studied. Spectrophotometric method was used to check the ability of bacteria to form biofilm and evaluated the role of waters onto ability of P. aeruginosa to form biofilm. The current study showed that all environmental isolates of P. aeruginosa had a good ability to form biofilm onto polystyrene microtiter plate. PAE1 showed the maximum ability of biofilm formation onto polystyrene microtiter plate. The water that collected from different places such as well water, river water, sewage water, distilled water, tap water and lake water showed negative effect (P
Keywords: Biofilm, Pseudomonas aeruginosa, polystyrene, polyvinyl chloride